A method for preparing sulfide single atom photocatalytic material

By using organic amine ligands to disperse metal sources and establish a metal-sulfur coordination structure on sulfide semiconductors, the problem of difficult to efficiently prepare single-atom metal catalysts in the prior art under mild conditions is solved, and a catalyst preparation with high stability and high activity is achieved, which is suitable for a variety of photocatalytic applications.

CN116586080BInactive Publication Date: 2025-04-01SHUNDE INNOVATION SCHOOL UNIVERSITY OF SCIENCE & TECHNOLOGY BEIJING
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210856443.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-19
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult to efficiently prepare high loaded single-atom metal catalysts under mild conditions in the prior art, and the high-temperature calcination or low-temperature photoreduction reaction of traditional methods leads to poor catalyst stability.

Method used

By dispersing the metal source with organic amine ligands, a coordination complex is formed to prevent the aggregation of metal precursors and sulfide is synchronized with zinc salt or cadmium salt, a strong coupling metal-sulfur coordination structure is established, and finally, the intercalated amine is removed through hydrothermal reaction to prepare a high-stability and high-activity sulfide semiconductor photocatalytic material modified by metal single atoms.

Benefits of technology

It has achieved efficient preparation of high-stability and high-active single-atom catalytic sites under mild conditions, significantly improving the stability and catalytic performance of the catalyst, and is suitable for photocatalytic decomposition of water to produce hydrogen and degradation of organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116586080B_ABST
    Figure CN116586080B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a sulfide photocatalytic material modified with a metal single atom, specifically adopting an organic amine to coordinate with a metal ion to effectively disperse a metal source, performing sulfidation in a solvent thermal process and coordinating with an organic amine to intercalate the metal single atom to stabilize the metal single atom in the sulfide lattice, and removing the intercalated amine by a hydrothermal reaction to obtain a single-atom-modified sulfide nano-photocatalytic material. This synthesis strategy is proposed for the first time and can be extended to the synthesis and preparation of single-atom catalysts of different metal elements (such as Pt, Ru, Ag, Ni), and the prepared single-atom structure is stable and has high catalytic activity. The preparation scheme has mild reaction conditions and high synthesis efficiency, and the prepared high-activity and high-stability sulfide single-atom catalytic material has broad application prospects in the fields of photocatalytic decomposition of water for hydrogen evolution, photocatalytic degradation of the organic pollutant phenol, and photocatalytic sterilization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano material preparation and photocatalysis, and specifically relates to a method for preparing a sulfide semiconductor photocatalytic material modified by a metal single atom. Background Art

[0002] Single-atom metal catalysts have a unique coordination environment and 100% atomic utilization, and have become a frontier in catalytic research. Thermodynamically, single atoms have high surface energy, which easily leads to atomic agglomeration and catalyst instability. Conventional single-atom synthesis methods have problems such as high energy consumption, harsh conditions, cumbersome procedures, uncontrollable and low loading, which seriously hinder the development of single-atom catalysts. Therefore, how to simply and efficiently prepare high-loading single-atom metal catalysts under mild conditions is an important challenge at present.

[0003] Traditional methods of preparing single-atom catalysts often randomly anchor metal atoms on the target carrier by means of high-temperature calcination or photoreduction. However, the preparation of single-atom catalysts is very sensitive to calcination temperature. Slight changes in high-temperature calcination conditions can easily lead to sintering of metal atoms and destroy the original coordination structure. Low-temperature photoreduction reaction conditions are mild, but the weak coupling between metal atoms and the carrier is not conducive to establishing a stable coordination structure between the two, resulting in poor stability of the catalyst during use. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a sulfide semiconductor photocatalytic material modified with a high stability and high activity by using the interaction between the lone pair of -NH2 electrons in the organic amine ligand and the empty d orbital of the metal to form a coordination complex that effectively disperses the metal source, prevents the aggregation of metal precursors during the thermal reaction, and coordinates the synchronous sulfurization of zinc salts or cadmium salts to form an organic and inorganic sulfide hybrid with amine intercalation, anchoring the metal single atom in the zinc sulfide or cadmium sulfide lattice, and establishing a metal-sulfur coordination structure with a strong coupling effect. Then, after the intercalated amine is removed by hydrothermal reaction, a metal single atom-modified zinc sulfide or cadmium sulfide nanophotocatalyst is obtained, thereby realizing the construction of a single-atom catalytic site with high stability. To achieve the above purpose, the present invention adopts the following technical scheme:

[0005] A method for preparing a sulfide single-atom photocatalytic material, the preparation method comprising the steps of:

[0006] (1) Dispersing the metal source with an organic amine: dispersing a metal precursor in an organic amine, mixing well, adding a zinc salt or cadmium salt aqueous solution, and continuously mixing well at room temperature to obtain a metal dispersion coordinated by an organic amine; the molar ratio of the metal precursor to the zinc salt or cadmium salt is 1-20:1000, and the concentration of the zinc salt or cadmium salt aqueous solution is 0.2-1.0 mol / L;

[0007] (2) Solvothermal vulcanization reaction: adding thiourea to the metal dispersion obtained in step (1) to dissolve, transferring the obtained mixed solution to a container for solvent thermal vulcanization reaction, collecting the product, washing and drying to obtain an organic-inorganic hybrid sulfide doped with a metal single atom, wherein the molar ratio of the thiourea to the zinc salt or cadmium salt is greater than 1:1, and the excess thiourea ensures complete metal vulcanization; the solvent thermal vulcanization reaction is carried out at 160-200° C. for 10-16 hours;

[0008] (3) Removal of coordinated amine by hydrothermal reaction: The metal single atom-doped sulfide organic-inorganic hybrid obtained in step (2) is dispersed in deionized water to completely dissolve it, and then subjected to a hydrothermal reaction. The product is collected, washed, and dried to obtain a single atom-modified sulfide photocatalytic material; the hydrothermal reaction is carried out at 140-160° C. for 3-6 hours.

[0009] Furthermore, the metal precursor in step (1) is selected from one of chloroplatinic acid, silver nitrate, nickel nitrate, cobalt nitrate, copper nitrate or ruthenium trichloride.

[0010] Furthermore, the organic amine multidentate ligand material in step (1) is selected from one of ethylenediamine, diethylenetriamine, propylenediamine and tetramethylethylenediamine.

[0011] Furthermore, the zinc salt or cadmium salt in step (1) is selected from zinc nitrate hexahydrate, zinc acetate dihydrate, zinc chloride, cadmium nitrate tetrahydrate, cadmium acetate dihydrate, and cadmium chloride.

[0012] Furthermore, the washing in step (2) is performed by washing with anhydrous ethanol and deionized water alternately for 2-4 times, and the drying is performed in a vacuum environment at 60-80° C. for 6-8 hours.

[0013] Furthermore, the washing in step (3) is performed by washing with deionized water for 2-4 times, and the drying is performed in a vacuum environment at 60-80° C. for 6-8 hours.

[0014] The beneficial effects of the present invention are:

[0015] (1) In the preparation scheme of this single-atom photocatalytic material, the coordination and dispersion effect of organic amines avoids metal agglomeration during the thermal reaction and ensures the high dispersion of single atoms; the sulfurization reaction establishes a metal-sulfur coordination structure with strong coupling, realizing the construction of highly stable single-atom catalytic sites on the sulfide substrate.

[0016] (2) In the photocatalytic material prepared by the scheme of the present invention, the metal single atom can not only serve as the active center of the reaction, but also effectively promote the separation of electron-hole pairs and regulate the kinetics of surface catalytic reactions, showing great potential in application fields such as photocatalytic decomposition of water to produce hydrogen, photocatalytic degradation of the organic pollutant phenol, and photocatalytic sterilization.

[0017] The method provided by the invention has mild reaction conditions, simple operation process, short reaction cycle and high repeatability. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The platinum single atom modified zinc sulfide photocatalytic material (Pt SA -ZnS) scanning transmission electron microscope image with spherical aberration correction.

[0019] Figure 2 Inventive Example 1 The platinum single atom modified zinc sulfide photocatalytic material (Pt SA -ZnS) XPS Pt 4f spectrum.

[0020] Figure 3 The platinum single atom modified zinc sulfide photocatalytic material (Pt SA -ZnS) under visible light irradiation.

[0021] Figure 4 The platinum single atom modified zinc sulfide photocatalytic material (Pt SA -ZnS) stability test in visible light photocatalytic hydrogen production reaction.

[0022] Figure 5 The platinum single atom modified zinc sulfide catalytic material (Pt SA / ZnS) in the visible light light catalytic hydrogen production reaction and stability test.

[0023] Figure 6 The silver single atom modified zinc sulfide photocatalytic material (Ag SA -ZnS) tested antibacterial sample colony counts and comparative blank sample colony counts.

[0024] Figure 7 The nickel single atom modified zinc sulfide photocatalytic material (Ni SA -ZnS) under visible light irradiation to degrade the organic pollutant phenol. DETAILED DESCRIPTION

[0025] The present invention will be further illustrated below in conjunction with specific embodiments. It should be understood that these embodiments are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art will make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0026] Example 1

[0027] (1) Since chloroplatinic acid is a block crystal that is difficult to weigh and has strong hygroscopicity, its aqueous solution was used for the experiment. 1.0 mL of chloroplatinic acid aqueous solution (0.02 mol / L) was dropped into 50 mL of ethylenediamine and stirred at room temperature for 20 minutes. 2 mmol (0.595 g) of zinc nitrate hexahydrate was dissolved in 10 mL of deionized water and homogenized by ultrasound. The two solutions were then mixed and stirred for 30 minutes.

[0028] (2) 4 mmol thiourea (0.304 g) was added to the transparent solution obtained in step (1) and stirred for 10 minutes. The mixed solution was then transferred to an autoclave and reacted at 180° C. for 12 hours. The product was collected and washed alternately with anhydrous ethanol and deionized water for 3 times and dried in a vacuum environment at 70° C. for 7 hours to obtain an organic-inorganic hybrid of zinc sulfide doped with a single platinum atom.

[0029] (3) 0.1 g of the zinc sulfide organic-inorganic hybrid modified with a single platinum atom obtained in step (2) was dispersed in 70 mL of deionized water, ultrasonicated for 10 minutes to completely dissolve it, and then reacted at 150° C. for 5 hours. The product was collected, washed with deionized water 3 times, and dried in a vacuum environment at 70° C. for 7 hours to obtain a zinc sulfide photocatalytic material modified with a single platinum atom (Pt SA -ZnS).

[0030] The obtained Pt SA -ZnS sample spherical aberration corrected scanning transmission electron microscope image Figure 1 As shown, it shows that in Pt SA - Platinum is distributed in ZnS in the form of single atoms; Figure 2 Medium Pt SA -The XPS Pt 4f spectrum of ZnS shows that no 0-valent metal platinum is generated, that is, the coordination effect of ethylenediamine ensures the atomic dispersion of the platinum component;

[0031] The obtained Pt SA -ZnS sample decomposition of water to produce hydrogen under visible light irradiation: First, 1 mg Pt SA -ZnS photocatalyst was dispersed in 20mL 0.1M Na2S / Na2SO3 aqueous solution with constant stirring and placed in a closed system for photocatalytic reaction. The reaction system was bubbling with nitrogen to remove air to ensure that the reactor was in an anaerobic state. A 300WXe lamp (λ>420nm) was used for irradiation for 2 hours. After the reaction, the volume of H2 was measured by gas chromatograph to calculate the reaction rate. Figure 3 Comparison of hydrogen production rate under visible light irradiation, Pt SA -ZnS is 84 times higher than pure ZnS, and the performance does not decrease significantly after 30 hours of cyclic reaction ( Figure 4 ), proving that the strong Pt-S anchoring effect formed by the sulfurization reaction ensures the good stability of the Pt single atom.

[0032] Comparative Example 1

[0033] (1) 2 mmol (0.595 g) of zinc nitrate hexahydrate was dissolved in 70 mL of deionized water and homogenized by ultrasound. Then 4 mmol of thiourea (0.304 g) was added to the above transparent solution and stirred for 10 minutes. The mixed solution was then transferred to an autoclave for solvothermal reaction, and the product was collected, washed and dried to obtain a zinc sulfide matrix material.

[0034] (2) Disperse 0.2 mmol of the zinc sulfide matrix material in step (1) in a mixed solution of 10 mL of triethanolamine and 60 ml of deionized water, and dissolve it completely by ultrasonication for 10 minutes. Add 1.0 mL of chloroplatinic acid aqueous solution (0.02 mol / L) and stir evenly. Purify the mixed system with nitrogen for 30 minutes to remove air and ensure that the reactor is in an anaerobic state. Then continue stirring under a 300 W Xe lamp (λ>420 nm) at room temperature and irradiate for 30 minutes. Finally, centrifuge and wash repeatedly with deionized water, and vacuum dry to obtain a zinc sulfide nanomaterial (Pt SA / ZnS).

[0035] The obtained Pt SA / ZnS sample decomposition of water to produce hydrogen under visible light irradiation: First, 1 mg Pt SA The ZnS photocatalyst was dispersed in 20 mL of 0.1 M Na2S / Na2SO3 aqueous solution with constant stirring and placed in a closed system for photocatalytic reaction. The air was removed from the reaction system by nitrogen bubbling to ensure that the reactor was in an anaerobic state. A 300 W Xe lamp (λ>420 nm) was used to irradiate the reaction for 2 hours. After the reaction, the volume of H2 was measured by gas chromatograph to calculate the reaction rate. Figure 5 As shown, the obtained Pt SA The hydrogen production rate of the / ZnS sample under visible light irradiation is 27 times higher than that of pure ZnS. The performance decreases by 25% after 24 hours of cycle reaction and by about 50% after 36 hours of cycle reaction, showing a significant improvement over the Pt in Example 1. SA -ZnS samples have poor catalytic performance and stability.

[0036] Example 2

[0037] (1) Add 0.02 mmol of silver nitrate to 50 mL of propylene diamine solution and stir continuously for 20 minutes at room temperature in the dark. Dissolve 2 mmol (0.595 g) of zinc nitrate hexahydrate in 10 mL of deionized water and homogenize with ultrasound. Then mix the two solutions and stir continuously for 30 minutes.

[0038] (2) 4 mmol thiourea (0.304 g) was added to the transparent solution obtained in step (1) and stirred for 10 minutes. The mixed solution was then transferred to an autoclave and reacted at 160° C. for 12 hours. The product was collected and washed alternately with anhydrous ethanol and deionized water for 3 times and dried in a vacuum environment at 60° C. for 6 hours to obtain an organic-inorganic hybrid of zinc sulfide doped with a single silver atom.

[0039] (3) 0.1 g of the organic-inorganic hybrid zinc sulfide doped with silver single atoms obtained in step (2) was dispersed in 70 mL of deionized water, ultrasonicated for 10 minutes to completely dissolve it, and then reacted at 140° C. for 3 hours. The product was collected, washed with deionized water 3 times, and dried in a vacuum environment at 60° C. for 6 hours to obtain a silver single atom-modified zinc sulfide photocatalytic material (Ag SA -ZnS).

[0040] Ag SA -ZnS samples were tested for photocatalytic bactericidal performance: an equal amount of target photocatalytic bactericidal agent was added to the phosphate buffer containing the same concentration of Escherichia coli, and after adsorption equilibrium in a constant temperature dark shaker, the bacteria were killed by irradiation with a 300W cold light source xenon lamp for 1 hour, and then 100μL of bacterial suspension was evenly spread on the agar plate. After being cultured in a constant temperature incubator overnight, it was found that there were more dispersed colonies in the culture medium without the addition of photocatalytic material, and the addition of Ag SA -ZnS photocatalytic material in the culture medium has zero colony count ( Figure 6 ), proving that the sterilization rate is greater than 99%, with significant disinfection and bactericidal properties.

[0041] Example 3

[0042] (1) Add 0.02 mmol nickel nitrate to 50 mL ethylenediamine solution and stir continuously at room temperature for 20 minutes. Dissolve 2 mmol (0.595 g) zinc nitrate hexahydrate in 10 mL deionized water and homogenize with ultrasound. Then mix the two solutions and stir continuously for 30 minutes.

[0043] (2) 4 mmol thiourea (0.304 g) was added to the transparent solution obtained in step (1) and stirred for 10 minutes. The mixed solution was then transferred to an autoclave and reacted at 160° C. for 12 hours. The product was collected and washed alternately with anhydrous ethanol and deionized water for 3 times and dried in a vacuum environment at 60° C. for 6 hours to obtain an organic-inorganic hybrid of zinc sulfide doped with a single nickel atom.

[0044] (3) 0.1 g of the zinc sulfide organic-inorganic hybrid doped with nickel single atoms obtained in step (2) was dispersed in 70 mL of deionized water, ultrasonicated for 10 minutes to completely dissolve it, and then reacted at 140° C. for 3 hours. The product was collected, washed with deionized water 3 times, and dried in a vacuum environment at 60° C. for 6 hours to obtain a zinc sulfide photocatalytic material modified with nickel single atoms (Ni SA -ZnS).

[0045] Ni SA -ZnS sample for photocatalytic degradation test of organic pollutant phenol: weigh 10 mg Ni SA -ZnS catalyst was added to 100ml of phenol solution (10mg / L), stirred and ultrasonicated to fully disperse the catalyst, and then the system was placed in constant temperature cooling water at 16℃, stirred and protected from light for 1h to achieve adsorption equilibrium. After one hour, irradiation with a 300w xenon lamp (AM 1.5 solar filter) was started, and the illumination time was 2h. Samples were taken every 10 minutes. After sampling, centrifugation was carried out in time, and the phenol concentration of the supernatant was tested using a UV-visible spectrophotometer. Figure 7 As shown, adding Ni SA -The degradation rate of the phenol solution of ZnS photocatalytic material is greater than 99% after 60 minutes, which shows that it has significant catalytic performance.

[0046] Example 4

[0047] (1) 1.0 mL of chloroplatinic acid aqueous solution (0.02 mol / L) was dropped into 50 mL of diethylenetriamine solution and stirred continuously at room temperature for 20 minutes. 2 mmol (0.595 g) of zinc nitrate hexahydrate was dissolved in 10 mL of deionized water and homogenized by ultrasound. The two solutions were then mixed and stirred continuously for 30 minutes.

[0048] (2) 4 mmol thiourea (0.304 g) was added to the transparent solution obtained in step (1) and stirred for 10 minutes. The mixed solution was then transferred to an autoclave and reacted at 160° C. for 16 hours. The product was collected and washed alternately with anhydrous ethanol and deionized water for 3 times and dried in a vacuum environment at 70° C. for 7 hours to obtain an organic-inorganic hybrid of zinc sulfide doped with a single platinum atom.

[0049] (3) 0.1 g of the organic-inorganic hybrid zinc sulfide doped with a single platinum atom obtained in step (2) was dispersed in 70 mL of deionized water and completely dissolved by ultrasonication for 10 minutes. The reaction was then carried out at 150° C. for 5 hours, the product was collected, washed with deionized water 3 times, and dried in a vacuum environment at 70° C. for 7 hours to obtain a zinc sulfide photocatalytic material modified with a single platinum atom.

[0050] Example 5

[0051] (1) 1.0 mL of chloroplatinic acid aqueous solution (0.02 mol / L) was dropped into 50 mL of ethylenediamine solution and stirred continuously at room temperature for 20 minutes. 2 mmol (0.616 g) of cadmium nitrate tetrahydrate was dissolved in 10 mL of deionized water and homogenized by ultrasound. The two solutions were then mixed and stirred continuously for 30 minutes.

[0052] (2) 4 mmol thiourea (0.304 g) was added to the above transparent solution and stirred for 10 minutes. The mixed solution was then transferred to an autoclave and reacted at 160° C. for 16 hours. The product was collected and washed alternately with anhydrous ethanol and deionized water for 3 times and dried in a vacuum environment at 70° C. for 7 hours to obtain an organic-inorganic hybrid of cadmium sulfide doped with a single platinum atom.

[0053] (3) 0.1 g of the organic-inorganic hybrid cadmium sulfide doped with a single platinum atom obtained in step (2) was dispersed in 70 mL of deionized water and ultrasonicated for 10 minutes to completely dissolve it. The water was then reacted at 150° C. for 5 hours, the product was collected, washed with deionized water 3 times, and dried in a vacuum environment at 70° C. for 7 hours to obtain a cadmium sulfide photocatalytic material modified with a single platinum atom.

Claims

1. A method for preparing a sulfide photocatalytic material modified by a metal single atom, characterized in that: The following steps are involved: (1) Dispersing the metal source with an organic amine: dispersing a metal precursor in an organic amine, mixing well, adding a zinc salt or cadmium salt aqueous solution, and continuously mixing well at room temperature to obtain a metal dispersion coordinated by an organic amine; the molar ratio of the metal precursor to the zinc salt or cadmium salt is 1-20:1000, and the concentration of the zinc salt or cadmium salt aqueous solution is 0.2-1.0 mol / L; (2) Solvothermal vulcanization reaction: adding thiourea to the metal dispersion obtained in step (1) to dissolve, transferring the obtained mixed solution to a container for solvent thermal vulcanization reaction, collecting the product, washing and drying to obtain an organic-inorganic hybrid sulfide doped with a metal single atom, wherein the molar ratio of the thiourea to the zinc salt or cadmium salt is greater than 1:1, and the excess thiourea ensures complete metal vulcanization; the solvent thermal vulcanization reaction is carried out at 160-200° C. for 10-16 hours; (3) Removal of coordinated amine by hydrothermal reaction: The metal single atom-doped sulfide organic-inorganic hybrid obtained in step (2) is dispersed in deionized water to completely dissolve it, and then subjected to a hydrothermal reaction. The product is collected, washed, and dried to obtain a single atom-modified sulfide photocatalytic material; the hydrothermal reaction is carried out at 140-160° C. for 3-6 hours.

2. The preparation method according to claim 1, characterized in that: The metal precursor in step (1) is selected from one of chloroplatinic acid, silver nitrate, nickel nitrate, cobalt nitrate, copper nitrate or ruthenium trichloride.

3. The method according to claim 1, characterized in that: The organic amine in step (1) is selected from one of ethylenediamine, diethylenetriamine, propylenediamine and tetramethylethylenediamine.

4. The preparation method according to claim 1, characterized in that: The zinc salt or cadmium salt in step (1) is selected from zinc nitrate hexahydrate, zinc acetate dihydrate, zinc chloride, cadmium nitrate tetrahydrate, cadmium acetate dihydrate, and cadmium chloride.

5. The preparation method according to claim 1, characterized in that: The washing in step (2) is performed by alternating anhydrous ethanol and deionized water for 2-4 times, and the drying is performed in a vacuum environment at 60-80° C. for 6-8 hours.

6. The preparation method according to claim 1, characterized in that: The washing in step (3) is performed by washing with deionized water for 2-4 times, and the drying is performed in a vacuum environment at 60-80° C. for 6-8 hours.

Citation Information

Patent Citations

  • Method for preparing metal sulfide / amine-hybrid nanomaterials and metal sulfide nanomaterials

    CN107572581A

  • Metal monoatom based material for room-temperature catalytic purification of VOCs and preparation method for metal monoatom based material

    CN110773158A

  • Binary Cu-S cluster compound containing transition metal complex ions and solvothermal preparation method and application thereof

    CN111925382A